Transcriptome profiling defines a novel regulon modulated by the LysR-type transcriptional regulator MexT in Pseudomonas aeruginosa - Tian, Z.; Fargier, E.; Mac Aogáin, M.; Adams, C.; Wang, Y.; O'Gara, Fergal (Oxford University Press, 2009)
The LysR-family regulator MexT modulates the expression of the MexEF-OprN efflux system in the human pathogen Pseudomonas aeruginosa. Recently, we demonstrated that MexT regulates certain virulence phenotypes, including the type-three secretion system and early attachment independent of its role in regulating MexEF-OprN. In this study, transcriptome profiling was utilized to investigate the global nature of MexT regulation in P. aeruginosa PAO1 and an isogenic mexEF mutant. Twelve genes of unknown function were highly induced by overexpressing MexT independent of MexEF-OprN. A well-conserved DNA motif was identified in the upstream regulatory region of nine of these genes and upstream of mexE. Reporter fusion analysis demonstrated that the expression of the genes was significantly induced by MexT in P. aeruginosa and a heterogenous Escherichia coli strain and that the conserved sequence was required for this induction. The conserved DNA motif was further characterized as the MexT binding site by site-directed mutagenesis and electrophoretic mobility shift assays. Genes containing this conserved regulatory sequence were identified across other Pseudomonas species, and their expression was activated by MexT. Thus, a novel regulon directly modulated by MexT, that includes but is independent of mexEF-oprN, has been identified.